The Challenge of Predicting Economic Crises - Berg, Andrew (Economic Issues; Economic Issues ;, 2001)
The integration of financial markets around the world over the past decade has posed new challenges for policymakers. The speed with which money can be switched in and out of currencies and countries has increased with the efficiency of global communications, considerably shortening the time policymakers have to respond to emerging crises. This pamphlet takes alook at attempts by economists to predict crises by developing early warning systems to signal when trouble may be brewing in currency markets and banking systems.